ANALYSIS OF THE EXTERNAL ENVIRONMENT AND INTERNAL CONTROL OF COMPANY PERFORMANCE - Hikmar Abdul Majid (Inovbiz: Jurnal Inovasi Bisnis, 2021)
The success of performance is not only from a historical financial aspect, but more than that, from non-financial factors that have a much greater contribution. The research objective is to analyze the environment, internal, and company performance. The method used in this research is a descriptive and associative approach with a quantitative approach. The sampling technique used in this study used saturated sampling or often referred to as census and in this case only PT Ultimedia Group Saudara's employees could get 58 people using the saturated sampling technique. The data analysis technique used is multiple linear regression analysis, including the coefficient of determination, multiple correlation coefficients, partial test (T test), and simultaneous test (F test). The results showed that the external environment has an effect on company performance. Internal control affects company performance. The simultaneous test results (F test) show that the external environment and control have an effect on company performance.